ATSAR AL-QUR’AN AL-KARIM FI AL-LUGHAH AL-‘ARABIYYAH FI DAU ‘ILM AL-LUGHAH AL-HADIS - Dawood, Mohamed (Indonesian Journal of Islamic Literature and Muslim Society, 2019)
This article discussed the influence of the Quran on Arabic in the perspective of modern linguistics. With a linguistic approach, this article finds seven aspects of language that occur in the impact of the Quran on Arabic, namely: preservation of Arabic, the stability of Arabic, the unification of Arabic dialects, enrichment and development of Arabic, refinement of Arabic and the spread of Arabic. These seven linguistics aspects certainly make Arabic the only language in the world whose linguistic rules do not change, both in terms of phonology, morphology, syntax or semantics, which does not occur in any word in the world. In this world, there have been many languages that have died because of the death of their owners, or languages that are weak because of the weakness of their owners. This condition is different from Arabic, which is the language of the Quran. The language relations between Arabic and the Qur'an have made this language sustainable until then.